Asociación entre presión arterial media alta en el primer trimestre y preeclampsia en gestantes nulíparas - Hospital Regional Docente de Trujillo - Díaz Silva, Carlos Jeiner (2019)
Objective: To determine whether high mean arterial pressure (MAP) in the first trimester is associated with preeclampsia in nulliparous pregnant women admitted to Hospital Regional Docente de Trujillo (HRDT) at period 2012-2017. Materials and methods: This is a retrospective study of cases and controls. Clinical records of 171 patients were reviewed. The group of patients who presented preeclampsia was 57 (cases) and the group of patients who did not present preeclampsia was 114 (controls). Chi square test and Odds Ratio (OR) with 95% confidence interval (95% CI) were used for statistical analysis. Results: The association between high MAP (MAP≥72mmHg) in the first trimester and preeclampsia in nulliparous pregnant women admitted to HRDT was statistically significant (OR: 2.87, 95% CI: 1.47-5.62). Conclusions: High MAP in the first trimester is significantly associated with preeclampsia in nulliparous pregnant women admitted to HRDT at period 2012-2017